2012
DOI: 10.1007/s00276-012-0992-1
|View full text |Cite
|
Sign up to set email alerts
|

Anatomo-radiological study of the superior semicircular canal dehiscence of 37 cadaver temporal bones

Abstract: This study emphasizes the limitations of CT imaging, with a risk of false positives to take into account when interpreting the images. The 3D reconstructions also give too many false positives to be used alone and make an accurate diagnosis. The diagnosis of SSCC dehiscence will therefore remain clinical. Complementary and instrumental radiological examinations should be performed only to confirm this clinical suspicion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Only tiny focal areas of apparent bone loss were required to be categorized as dehiscence; however, as previously shown in temporal bone histologic studies, bone thickness of Ͻ0.1 mm can be falsely read as dehiscent. 33,34 We also found a higher incidence of sigmoid sinus diverticula in our control cohort than described in previous studies: 8% compared with 0.5% reported by Grewal et al, 14 which may reflect differences in the demographic studied or possibly be due to sampling bias inherent in our smaller sample size.…”
Section: Discussionsupporting
confidence: 44%
“…Only tiny focal areas of apparent bone loss were required to be categorized as dehiscence; however, as previously shown in temporal bone histologic studies, bone thickness of Ͻ0.1 mm can be falsely read as dehiscent. 33,34 We also found a higher incidence of sigmoid sinus diverticula in our control cohort than described in previous studies: 8% compared with 0.5% reported by Grewal et al, 14 which may reflect differences in the demographic studied or possibly be due to sampling bias inherent in our smaller sample size.…”
Section: Discussionsupporting
confidence: 44%
“…The importance of not relying solely on CT to diagnose superior semicircular canal dehiscence and of correlating CT finding to clinical findings and other investigations has been clarified. [23][24][25][26] This is due to the high risk of false positives when performing CT analysis for superior semicircular canal dehiscence. One paper reported that when a diagnosis was based solely on CT scans, 80 per cent of cases were false positives.…”
Section: Discussionmentioning
confidence: 99%
“…However, no dehiscence was found by microscopic analysis. 23 In a larger population, Tavassolie et al compared the surgical and CT findings of 34 surgically confirmed superior semicircular canal dehiscence patients. 24 They concluded that CT can overestimate the dehiscence size and can result in false positives for dehiscence detection.…”
Section: Investigationsmentioning
confidence: 97%
“…9,12,49 However, even HRCT can produce falsepositive results if the canal roof is thinner than the image resolution slice thickness, as might be expected given an average SSC roof thickness of 1 mm in cadaveric studies. 23,51,58,61,79 Osteoporosis can also lead to a false-positive reading because of lack of calcium in the imaged bone. Reformatted images parallel (Pöschl's plane) or perpendicular (Stenver's plane) to the SSC may aid visualization of a dehiscence (Fig.…”
Section: Imagingmentioning
confidence: 99%